Early MP-ASI Supplementation Impact in Infants and Toddlers Aged 6 to 24 Months - Octaviana, Amrina; Roslina, Roslina; Indrasari, Nelly (JURNAL INFO KESEHATAN, 2024)
The highest rate of solid or semi-solid feeding occurs at the age of 4-5 months in 32.7% of the 488 sample children, according to data from the Indonesian Demographic and Health Survey, and the highest rate of early supplementation of drinking occurs at 2-3 months in 24.7% of the 506 sample children. This research also continues the results of previous research, where the research was to determine the dominant factors in giving MP-ASI to babies and toddlers. The research results were obtained from 132 babies and toddlers, of whom 44 (33.3%) had received early MP-ASI. This study aimed to determine the effect of early complementary feeding on growth and development in infants and toddlers aged 6–24 months in the Banjar Baru PKM area, Tulang Bawang Regency, in 2022. This type of research is retrospective with stratified random sampling, with a sample of 132 mothers with infants and toddlers aged 6–24 months. Bivariate analysis using the Chi-Square test and multivariate analysis with the Logistics Regression Test. The results of the study showed that more than half, namely 62.1% of respondents, were in favor of giving early complementary feeding to infants and toddlers in the risk category in the work area of the Banjar Baru Health Center, Tulang Bawang Regency, in 2022. The statistical test results also found that there was a significant effect between the behavior of giving MP to infants and toddlers with growth (p-value = 0.0001, OR = 3.273) and development (p-value = 0.000, OR = 10.353) in the Banjar Baru Public Health Center, Tulang Bawang Regency in 2022. In order to prevent early complementary feeding in infants and toddlers, it is suggested that pregnant women be educated about the effects of early complementary feeding on their children's growth and development from 6 to 24 months of age. reactivating the role of Integrated Service Post (Posyandu) and health cadres in community activities for early detection of growth and development of infants and toddlers, identifying anomalies early so they can immediately receive referrals for treating developmental disorders in infants and toddlers in the Banjar Baru health center, Tulang Bawang district, in 2022.